Assessment of Groundwater Salinity and Sodicity for Irrigation in Sabratha, Libya. (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
In the management of water resources, quality of water is just as important as its quantity. The main aim of this research study was to assess the variability of groundwater parameters to develop water quality in Sabratha city and its suitability for irrigation purpose. Ten samples from different sites of selected study area were collected and analyzed for major cations and anions. The suitability of the groundwater for irrigation was evaluated based on electrical conductivity (EC), Sodium Percentage (Na%), Sodium Absorption Ratio (SAR), Soluble Sodium Percentage (SSP), Permeability Index (PI), and Potential Salinity (PS). The obtained results show that the majority of the groundwater samples were categorized as doubtful to unsuitable for irrigation purposes. The USSLS chart indicating water of high to very high salinity, and low to medium sodium and water with good to moderate quality. The Na% and the resulting Wilcox diagram classify the groundwater as doubtful to unsuitable category. On the Wilcox diagram, the water samples fell into three categories, about 50% of the water samples were good to doubtful category for irrigation, and the other samples fell in the category unsuitable for irrigation. The Doneen diagram showed that more than 50% of the groundwater samples are distributed in class III and are unsuitable for irrigation uses. Generally, the majority of groundwater samples in the study area were categorized as doubtful to unsuitable for irrigation purposes.
Keywords: SAR; Na%; USSLS; Wilcox; Irrigation